Description Of Sleep Quality In Patients With Chronic Obstructive Pulmonary Disease At Imelda Pekerja Indonesia General Hospital Medan - Hasibuan, Ali Sabela; Dewi, Ratna; Damanik, Hamonangan (SEAN Institute, 2023)
Sleep quality is the sleep that a person gets which is useful for getting freshness and fitness when waking up from sleep and can be assessed by the number of hours of sleep. Chronic Obstructive Pulmonary Disease (COPD) is a chronic inflammation that leads to long-lasting narrowing of the airways caused by destruction of the alveolar walls. The aim of the research is to determine the description of the sleep quality of patients with chronic obstructive pulmonary disease (COPD) at the Imelda Pekerja IndonesiaGeneral Hospital, Medan in 2021. This research uses a descriptive method, a cross sectional approach with a sampling technique using nonprobability sampling with a sampling method, namely consecutive sampling involving 31 respondents. The instrument used was the Pittsburgh Sleep Quality Index (PSQI) sleep quality questionnaire. The results of this study were based on the sleep quality of 31 COPD patients in the orchid room at the Imelda Pekerja IndonesiaGeneral Hospital, Medan. The majority of respondents had poor sleep quality, 21 people (67.7%) and the minority had good quality, 10 people (32, 3%). It is hoped that it can be used for basic data and developed for subsequent research by adding respondents, conducting research on the description of patients with chronic obstructive pulmonary disease (COPD) in improving sleep quality, and before conducting interviews so that researchers can better understand the material. 7%) and minorities have good qualities as many as 10 people (32.3%). It is hoped that it can be used for basic data and developed for subsequent research by adding respondents, conducting research on the description of patients with chronic obstructive pulmonary disease (COPD) in improving sleep quality, and before conducting interviews so that researchers can better understand the material. 7%) and minorities have good qualities as many as 10 people (32.3%). It is hoped that it can be used for basic data and developed for subsequent research by adding respondents, conducting research on the description of patients with chronic obstructive pulmonary disease (COPD) in improving sleep quality, and before conducting interviews so that researchers can better understand the material.